Biohydrogen production from industrial wastewater: An overview. (September 2019) - Preethi,; Usman, T.M. Mohamed; Rajesh Banu, J.; Gunasekaran, M.; Kumar, Gopalakrishnan
Abstract: Biohydrogen production from industrial wastewater has been a focus of interest in recent years. The in depth knowledge in lab scale parameters and emerging strategies are needed to be investigated in order to implement the biohydrogen production process at large scale. The operating parameters have great influence on biohydrogen productivity. With the aim to gain major insight into biohydrogen production process, this review summarizes recent updates on dark fermentation, inoculum pretreatment methods, operating parameters (hydraulic retention time, organic loading rate, pH, temperature, volatile fatty acids, bioreactor configuration, nutrient availability, partial pressure etc.). The challenges and limitations associated with the biohydrogen production are lack of biohydrogen producers, biomass washout and accumulation of metabolites are discussed in detail. The advancement strategies to overcome these limitations are also briefly discussed. Graphical abstract: Unlabelled Image Highlights: Industrial wastewater is a cheap substrate for profitable biohydrogen production. Pretreatment of inoculum enriches the selective hydrogen producing microbes. Immobilization is the advanced technique to surpass biomass washout in bioreactors. Process integration is a plausible choice to overcome the accumulated metabolites.